2018
DOI: 10.1128/mcb.00250-17
|View full text |Cite
|
Sign up to set email alerts
|

Id2 Determines Intestinal Identity through Repression of the Foregut Transcription Factor Irx5

Abstract: The cellular components and function of the gastrointestinal epithelium exhibit distinct characteristics depending on the region, e.g., stomach or intestine. How these region-specific epithelial characteristics are generated during development remains poorly understood. Here, we report on the involvement of the helix-loop-helix inhibitor Id2 in establishing the specific characteristics of the intestinal epithelium. Id2−/− mice developed tumors in the small intestine. Histological analysis indicated that the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…An earlier study on a small sample set of Wilms tumours indicated that low mRNA expression of both IRX3 and IRX5 correlates to poor prognosis in Wilms tumour [6]. However, in the present study, loss of IRX5 resulted in small, well-differentiated tumours, which suggests an oncogenic-like role for IRX5 in Wilms tumour, well in accordance with a recently proposed role as an oncogenic driver in prostate and colorectal cancer [39][40][41]. One plausible explanation for the seemingly contradictory role of IRX5 as a promotor of tumorigenesis on the one hand and the correlation of poor prognosis to its reduced mRNA expression on the other hand is its correlated expression with IRX3 in clinical material.…”
Section: Discussionsupporting
confidence: 90%
“…An earlier study on a small sample set of Wilms tumours indicated that low mRNA expression of both IRX3 and IRX5 correlates to poor prognosis in Wilms tumour [6]. However, in the present study, loss of IRX5 resulted in small, well-differentiated tumours, which suggests an oncogenic-like role for IRX5 in Wilms tumour, well in accordance with a recently proposed role as an oncogenic driver in prostate and colorectal cancer [39][40][41]. One plausible explanation for the seemingly contradictory role of IRX5 as a promotor of tumorigenesis on the one hand and the correlation of poor prognosis to its reduced mRNA expression on the other hand is its correlated expression with IRX3 in clinical material.…”
Section: Discussionsupporting
confidence: 90%
“…Irx5 is a downstream target of Hoxb4 (18). Moreover, repression of Irx5 was reported to be involved in small intestine development, and this repression was found to be exerted by Id2 (19) With respect to Irx5 in tumorigenesis, one study found that Irx5 was associated with metastasis in colorectal cancer (20). Irx3 has been found to have an antagonistic relationship with Irx5 in development of the proximal limbs and patterning of the anterior and proximal limb skeleton, and this was negatively regulated by Sonic hedgehog (Shh) signaling (21).…”
Section: Discussionmentioning
confidence: 99%
“…Primer sequences for RT-PCR analysis are as follows: Sox21 -forward, TACATGATCCCGTGCAACTG; and Sox21 -reverse, TTCGAGCTGGTCATTCACTG. PCR primer sequences for qRT-PCR and Actb primers for RT-PCR analysis were described previously [1] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…In total, 34 genes were differentially expressed in Id2 −/− embryo compared with Id2 +/+ embryo with criteria of fold change >2. Of these differentially expressed genes, 14 genes were upregulated and 20 genes were downregulated in Id2 −/− embryo ( Table 1 ) [1] .…”
Section: Datamentioning
confidence: 99%